2006
DOI: 10.1120/jacmp.v7i4.2222
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the interplay effect in lung IMRT treatment using EDR2 films

Abstract: Intrafraction organ motion during the dynamic delivery of intensity‐modulated radiation therapy (IMRT) treatment of lung tumors may cause unexpected hot/cold spots within the target volume, due to the interplay effect between tumor motion and multileaf collimator (MLC) leaf motion. In the past, this has been investigated through theoretical analysis, computer simulation, and experimental measurement using an ionization chamber dosimeter. In the work presented here, the interplay effect was studied experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 24 publications
(13 reference statements)
1
52
0
4
Order By: Relevance
“…It has been shown that certain combinations of MLC sequence and target motion can give large dose discrepancies ( 1 , 2 ) for individual fractions. These effects generally average out when multiple fractions are used, ( 3 9 ) but Seco et al ( 1 ) found that this is not always the case (e.g., for step‐and‐shoot IMRT) and, for some situations, a dose error could still remain after multiple fractions.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that certain combinations of MLC sequence and target motion can give large dose discrepancies ( 1 , 2 ) for individual fractions. These effects generally average out when multiple fractions are used, ( 3 9 ) but Seco et al ( 1 ) found that this is not always the case (e.g., for step‐and‐shoot IMRT) and, for some situations, a dose error could still remain after multiple fractions.…”
Section: Introductionmentioning
confidence: 99%
“…From the figure, it is evident that dose delivery over multiple breathing cycles by reducing the dose rate would reduce the interplay effect. On average, the TCP pop reduction owing to interplay effect was reduced by approximately 1.5% with 300 MU min 21 compared with 600 MU min 21 . Although this is not a significant reduction for the range of motion assumed in this study, this indicates that reduced dose rate is beneficial for treating moving targets while no motion management techniques are used.…”
Section: Resultsmentioning
confidence: 90%
“…The effect of dose rate on TCP pop owing to interplay is studied for single-fraction treatments (as there is no significant difference for conventional fractionation) with 300 and 600 MU min 21 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations